Current Implementation of Digital Dentistry for Removable Prosthodontics in US Dental Schools. (15th April 2022) - Ishida, Yoshiki; Kuwajima, Yukinori; Kobayashi, Takuya; Yonezawa, Yu; Asack, Derek; Nagai, Manavi; Kondo, Hisatomo; Ishikawa-Nagai, Shigemi; Da Silva, John; Lee, Sang J.
Abstract : Objectives . Although digital technology has been widely integrated into dental education, there is limited literature investigating the extent of the integration of computer-aided design and computer-aided manufacturing (CAD-CAM) for removable systems in the dental curriculum. The purpose of this study was to assess the current implementation of CAD-CAM complete and partial dentures in predoctoral (PP) and advanced graduate prosthodontic (AGP) education in US dental schools. The study also aimed to identify potential barriers to its implementation in the dental curriculum. Methods . An online survey with 15 questions was created using online survey software. The survey was distributed to the directors of predoctoral prosthodontics in 56 schools and advanced graduate programs of prosthodontics in 52 schools listed in the 2018–19 American Dental Education Association (ADEA) Directory. Results . The percentage of programs (PP and AGP) implementing CAD-CAM complete dentures (CAD-CAM CDs) and CAD-CAM removable partial dentures (CAD-CAM RPDs) in their didactic, preclinical, and clinical curricula was recorded. CAD-CAM CDs are taught in didactic courses in 54.2% of PP and 65.2% of AGP. However, CAD-CAM RPDs are only taught in 37.5% of PP and 47.8% of AGP. Programs are largely limited by a lack of funds, resources, time, and faculty members. Conclusion . While digital technologies have indeed become more prevalent in dental education, many institutions face barriers to implementation. More research must be conducted in order to support the continued incorporation of digital technologies into dental education.